Analysis of fungal endophytes in Scottish Sitka spruce plantations shows extensive infections, novel host partners and gives insights into origins - Carly R. Anderson Stewart (2018)
© 2018 Blackwell Verlag GmbH This preliminary study identified the fungal endophytes of Sitka spruce (Picea sitchensis) in four Scottish plantations, analysed their recruitment possibilities and community structure across the sites, and identified the possible origins of the endophytes in this non-native host. Although Sitka spruce is native to north-western North America, it comprises a huge portion of Scottish forestry and is an economically vital timber tree. Needles from two age classes were collected and cultured for emerging endophyte isolates. Using a combination of morphological features and genetic sequencing of the nuclear ribosomal ITS regions of representative morphological types, 57 morphotypes were recorded which represented at least 15 different species, including a hypothesized sister species to the pathogen of Pseudotsuga menziesii in North America and Europe, Nothophaeocryptopus gaeumannii (previously P. gaeumannii) that was present at all sites tested. Diversity, recruitment, site, needle age and needle part effects are discussed. The phylogeny of Nothophaeocryptopus based on analysis of combined ITS and Tub2 sequence data is given in order to assess the relationship of the unknown endophyte to the Douglas fir pathogen N. gaeumannii.